2018
DOI: 10.1038/s41598-018-31374-w
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation of Transition Metal Dichalcogenides by a High-Power Femtosecond Laser

Abstract: Thin layer two-dimensional (2-D) transition metal dichalcogenide (TMD) materials have distinctive optoelectronic properties. Therefore, several methods including mechanical exfoliation, chemical vapor deposition, and liquid-phase exfoliation have been attempted to obtain uniform TMDs. However, such methods do not easily produce high-quality few-layer TMDs with high speed. Here, we report the successful fabrication of few-layer TMD materials by femtosecond laser irradiation. It shows that TMD samples can be exf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 37 publications
1
24
1
1
Order By: Relevance
“…3A. The much narrower PL spectrum (Supplementary Information S5) of Sample B than Sample A indicates that the former is cleaner (33), consistent with the general view that exfoliated TMD monolayers are usually less defective than the CVD grown monolayers (34,35). Surprisingly, during our measurement on over 10 TMD samples, we have systematically observed that the photoconductivity in exfoliated monolayers is always lower than that in CVD ones.…”
Section: Resultssupporting
confidence: 84%
“…3A. The much narrower PL spectrum (Supplementary Information S5) of Sample B than Sample A indicates that the former is cleaner (33), consistent with the general view that exfoliated TMD monolayers are usually less defective than the CVD grown monolayers (34,35). Surprisingly, during our measurement on over 10 TMD samples, we have systematically observed that the photoconductivity in exfoliated monolayers is always lower than that in CVD ones.…”
Section: Resultssupporting
confidence: 84%
“…Hence, even though the ME technique for obtaining high-quality 2D samples is attractive, its poor yield, 128 uncontrollable and irregular sample homogeneity, and not being scalable makes this technique unsuitable for almost any practical applications. 128,129 Chemical vapor deposition (CVD), on the other hand, is a scalable technique, where, unlike ME, large-scale single crystals of 2D-TMDs with uniform layer-thicknesses over lateral sizes reaching hundreds of micrometers can be produced. 52,130 In CVD, TMDs are typically grown using MoO 3 and X (X=S, Se, W etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we can obtain a large aspect ratio if we decrease the thickness of filler. According to the existing research, the preparation of two-dimensional nanomaterials generally includes a micro-mechanical exfoliation method [ 22 ], ball milling [ 23 , 24 ], laser exfoliation [ 25 ], liquid exfoliation [ 26 , 27 , 28 ], a lithium intercalation method [ 29 ] and chemical vapor deposition (CVD) [ 30 , 31 ]. Fan et al demonstrated a novel approach to fabricate boron nitride nanosheets (BNNS) via hypochlorite-assisted ball milling.…”
Section: Introductionmentioning
confidence: 99%